Does Argentine ant invasion affect prey availability for foliage-gleaning birds? - Estany-Tigerström, David; Bas, Josep Maria; Pons, Pere (Biological Invasions, 2009)
Food availability during the breeding season plays a critical role in reproductive success of insectivorous birds. Given that the invasive Argentine ant (Linepithema humile) is known to alter arthropod communities, we predicted that its invasion may affect the availability of food resources for coexisting foliage-gleaning birds. With this aim we studied, for 3 years, foliage arthropods occurring on cork oaks (Quercus suber) and tree heaths (Erica arborea) in invaded and non-invaded secondary forests of the northeastern Iberian Peninsula. Our results show that Argentine ants interact with arboreal foliage arthropods in a different manner than the native ants they displace do. The invasive ant impacted the arthropod community by reducing order diversity and ant species richness and by causing extirpation of most native ant species. Arthropod availability for foliage gleaners’ nestlings diminished in invaded cork oaks, mainly responding to the abundance and biomass depletion of caterpillars. Results suggest that the reproduction of canopyforaging foliage-gleaning species that mostly rely on caterpillars to feed their young could be compromised by the Argentine ant invasion. Thus, the Argentine ant could be promoting bottom-up effects in the trophic web through its effects on the availability of arthropod preys for insectivorous birds.
Keywords: arborea á; Biological invasion; biological invasion á erica; birds á; Erica arborea; Foliage arthropods; foliage arthropods á insectivorous; Insectivorous birds; Linepithema humile; linepithema humile á quercus; Quercus suber; suber

Does Argentine ant invasion affect prey availability for foliage-gleaning birds? - Estany-Tigerström, David; Bas, Josep Maria; Pons, Pere (Biological Invasions, 2009)
Food availability during the breeding season plays a critical role in reproductive success of insectivorous birds. Given that the invasive Argentine ant (Linepithema humile) is known to alter arthropod communities, we predicted that its invasion may affect the availability of food resources for coexisting foliage-gleaning birds. With this aim we studied, for 3 years, foliage arthropods occurring on cork oaks (Quercus suber) and tree heaths (Erica arborea) in invaded and non-invaded secondary forests of the northeastern Iberian Peninsula. Our results show that Argentine ants interact with arboreal foliage arthropods in a different manner than the native ants they displace do. The invasive ant impacted the arthropod community by reducing order diversity and ant species richness and by causing extirpation of most native ant species. Arthropod availability for foliage gleaners’ nestlings diminished in invaded cork oaks, mainly responding to the abundance and biomass depletion of caterpillars. Results suggest that the reproduction of canopyforaging foliage-gleaning species that mostly rely on caterpillars to feed their young could be compromised by the Argentine ant invasion. Thus, the Argentine ant could be promoting bottom-up effects in the trophic web through its effects on the availability of arthropod preys for insectivorous birds.
Keywords: arborea á; Biological invasion; biological invasion á erica; birds á; Erica arborea; Foliage arthropods; foliage arthropods á insectivorous; Insectivorous birds; Linepithema humile; linepithema humile á quercus; Quercus suber; suber